How carrots won the Trojan War : curious (but true) stories of common vegetables - Rupp, Rebecca (North Adams, MA : Storey Pub., 2011)
Vegetables are more than just food for humans--they've been characters, companions, and even protagonists throughout history. This is a delightful collection of little-known stories about the origins, legends, and historical significance of 23 of the world's most popular vegetables.
Vegetables in and out of the garden -- Asparagus seduces the King of France -- Beans beat back the Dark Ages -- Beets make Victorian belles blush -- Cabbage confounds Diogenes -- Carrots win the Trojan War -- Celery contributes to Casanova's conquests -- Corn creates vampires -- Cucumbers imitate pigeons -- An eggplant causes a holy man to faint -- Lettuce puts insomniacs to sleep -- Melons undermine Mark Twain's morals -- Onions offend Don Quixote -- Peas almost poison General Washington -- Peppers win the Nobel Prize -- Potatoes baffle the Conquistadors -- Pumpkins attend the World's Fair -- Radishes identify witches -- Spinach deceives a generation of children -- Tomatoes fail to kill Colonel Johnson -- Turnips make a viscount famous.
Includes index.
Includes bibliographical references and index.
Keywords: Vegetables -- History; Vegetable gardening -- History; Vegetable gardening; Vegetables; Vegetables -- History; Vegetable gardening -- History; History